Portable dedvices for cryosurgery and therapy - Mezhov-Deglin, L. P.; Kalmykova, Z. V.; Makova, M. K.; Lanin, A. N.; Petrusenko, I. V.; Shafranov, V. V. (Recent Contributions to Physics, 2015)
Cryosurgery is a surgical technique that employs freezing to destroy undesirable tissue. Although the prefix “cryo” (from the Greek word “kruos” for cold) usually refers to temperatures below 120K, cryosurgery deals with temperatures below the freezing temperature of tissue, i.e. about 273K.